The social construction of safety: Comparing three realities. (January 2015) - Blazsin, Hortense; Guldenmund, Frank
Highlights: Simultaneous appreciation/distance from organization's safety policy is analyzed. Local safety discourses depend on each group's organizational positioning. Heterogeneity of discourses results from a broken down culture development cycle. We shed new light on the dynamics behind the development of a safety culture. Abstract: This study focuses on the (development of) safety culture of a big gas distribution company. Using a social constructionist framework, we explore the discourses constructed by three of the organization's subgroups in relation to safety. Those groups, which are all situated at field level from a single working site, and therefore share a similar proximity to safety issues, occupy different hierarchical and functional positions. We assumed that each group may be considered as a specific social world, within which a specific perception of, and relationship with, safety is constructed, and that discourse analysis offers access to this construction. Individual semi-structured interviews were carried out to gather the discourses and analyzed in an ethno-methodological and conversation analysis perspective. Our discourse analysis allowed us to confirm our assumption by identifying that from one shared 'root' perception, three different constructions of safety stem. They appear to depend on both the group's specific jobs, and group positioning within the organization. Building on Berger and Luckmann's development cycle and on Weick's theory of sensemaking, we interpret those results as ensuing from a hiatus in the organization's rules enactment process and culture development cycle.